Self-regulation and high school athletes : an action research case study - Nachum, Adina (2018)
Self-regulatory skills are considered vital for proper child development, with some children not being able to self-regulate efficiently being put at high levels of risk for poor developmental outcomes (Zimmerman, 2007). A psychological skills training programme is one such avenue to teach self-regulatory skills to children. Research shows that children who take part in a psychological skills training from a young age are building a positive foundation for their future (Sharp et al., 2013). The purpose of this study is to identify whether high school athletes can develop self-regulation skills from partaking in a psychological skills training programme. Sixteen participants took part in the study with the inclusion criteria being female field hockey players between the ages of 13-17. The study used a mixed methods design and used the following methods: The adolescent self-regulatory inventory measure for pre and post self-regulatory levels of the programme, a post-game questionnaire to assess knowledge uptake, and a qualitative evaluation form to assess learnt knowledge. Quantitative data was analysed using descriptive statistics and qualitative was with thematic analysis. Results showed that all participants increased their self-regulation scores on the adolescent selfregulatory inventory and learnt one component of self-regulation – performance control. The highest responses to how mental skills helped players in a game were that it assisted participants to make better choices and stay calm. Overall, participants enjoyed the psychological skills training programme, wanted more sessions and time to apply skills and were able to develop some self-regulatory skills.